2006
DOI: 10.1016/j.jcv.2005.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Identification of viral agents associated with diarrhea in young children during a winter season in Beijing, China

Abstract: Enteric viruses play an important role in pediatric diarrhea during the winter season in China. A combination of microscopic examination of stool samples with specific EIA assays to detect virus antigen in stool specimens may be suitable for routine diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
41
3
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 21 publications
14
41
3
3
Order By: Relevance
“…The second most frequent norovirus genotype found in this study was GGII.b. Several studies have reported this genotype as a cause of sporadic and outbreak cases of gastroenteritits in children, and some of these studies suggested that GGIIb was closely associated with infections in children [36][37][38][39][40]. In this study, the highest rates of GGIIb detection were observed in January-February 2002 and the fall and winter of [2003][2004].…”
Section: Discussionmentioning
confidence: 51%
“…The second most frequent norovirus genotype found in this study was GGII.b. Several studies have reported this genotype as a cause of sporadic and outbreak cases of gastroenteritits in children, and some of these studies suggested that GGIIb was closely associated with infections in children [36][37][38][39][40]. In this study, the highest rates of GGIIb detection were observed in January-February 2002 and the fall and winter of [2003][2004].…”
Section: Discussionmentioning
confidence: 51%
“…The 50 μl RNA eluates were stored at −80°C until amplification of nucleic acid was performed. Primer characteristics and references for the amplification conditions of different PCR or nested PCR protocols used for nucleic acid detection of rotavirus, astrovirus, and norovirus were all described previously (Liu et al 2006;He et al 2008). Briefly a single-step RT-PCR reaction for viruses was performed with the following reaction condition: 10 mM Tris-HCl (pH 8.3), 50 mM KCl, 1.5 mM MgCl 2 , 0.2 mM dNTPs (Promega, Beijing, China), 200U M-MLV RT (Promega, Beijing, China), 2.5 U Ex-Taq DNA polymerase (TaKaRa, Dalian, China), 20 U RNasin (Promega, Beijing, China), and 1 M each of primers.…”
Section: Virus Concentrationmentioning
confidence: 99%
“…Ingestion of 10-100 viral particles is enough to cause disease (Gutiérrez-Aguirre et al 2009). The reported frequency of infection by RV, astrovirus (AV), and norovirus (NV) was 59%, 8%, and 6%, respectively, during the winter season (from December 2000 to March 2001) in Beijing (Liu et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The reported frequencies of infection by rotavirus, astrovirus, and norovirus were 59%, 8% and 6%, respectively, during the winter season (from December 2000 to March 2001) in Beijing Children's Hospital (Liu et al 2006). The infection was most commonly seen among children o5 years old hospitalized with acute diarrhea ) and 96.8% of children were infected under 3 years of age (Tong et al 2003).…”
Section: Introductionmentioning
confidence: 99%